1998
DOI: 10.1095/biolreprod59.6.1392
|View full text |Cite
|
Sign up to set email alerts
|

Inhibin Secretion in the Mare: Localization of Inhibin α, βA, and βB Subunits in the Ovary1

Abstract: To determine the source of circulating inhibin and estradiol-17beta during the estrous cycle in mares, the cellular localization of the inhibin alpha, betaA, and betaB subunits and aromatase in the ovary was determined by immunohistochemistry. Concentrations of immunoreactive (ir-) inhibin, estradiol-17beta, progesterone, LH, and FSH in peripheral blood were also measured during the estrous cycle in mares. Immunohistochemically, inhibin alpha subunits were localized in the granulosa cells of small and large fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
50
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 35 publications
7
50
0
Order By: Relevance
“…Granulosa cells of various sized follicles and theca cells of large follicles are the primary sources of inhibin during the estrous cycle of the mare [18][19][20]24]. Our previous studies have demonstrated the presence of inhibin α and inhibin/activin (β A and β B ) subunits in the interstitial cells of equine fetal ovaries, showing that the main source of large amounts of inhibins in fetal circulation is interstitial cells of the ovary and is not of maternal origin [25].…”
mentioning
confidence: 99%
“…Granulosa cells of various sized follicles and theca cells of large follicles are the primary sources of inhibin during the estrous cycle of the mare [18][19][20]24]. Our previous studies have demonstrated the presence of inhibin α and inhibin/activin (β A and β B ) subunits in the interstitial cells of equine fetal ovaries, showing that the main source of large amounts of inhibins in fetal circulation is interstitial cells of the ovary and is not of maternal origin [25].…”
mentioning
confidence: 99%
“…1 and 2) as described previously [14,15]. For inhibin α-subunit, a rabbit polyclonal antibody against [Tyro30]-porcine inhibin α-chain (1-30) diluted to 1:8000 in 0.5% (w/v) casein-Tris saline (CTS) was used as the primary antibody.…”
mentioning
confidence: 99%
“…In female mammals, granulosa cells within the ovarian follicles secrete inhibin [6]. In mares, plasma concentrations of immunoreactive inhibin are higher in the follicular phase of the estrous cycle than the luteal phase and show a reciprocal relationship with FSH concentrations [2,13,14,18]. Nagamine et al [14] identified inhibin α-, βB-and βA-subunits in both granulosa and theca cells of large ovarian follicles using immunohistochemistry, whereas, only inhibin α was detected in granulosa cells of small ovarian follicles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…66(1): [31][32][33][34][35] 2004 The physiological mechanisms responsible for limiting one follicular development and ovulation from multiple follicles during the normal follicular phase in the mare is not yet fully understood. Attempts at inducing multiple ovulation or promoting fertility in the mare with various treatments such as equine chorionic gonadotropin (eCG), equine pituitary extract and PGF 2 α have met with limited success [2,6,10,12,17,20]. Currently, crude pituitary extracts are the most reliable method for inducing multiple ovulations in the mare and this method usually results in one to four ovulations per cycle [5], but pituitary extracts are not readily available and the regimens required are relatively intensive.…”
mentioning
confidence: 99%